Geoffrey Andrew Holmes, Compiled Ordinances of the City of Council Bluffs 206-07 (1887) - (:unkn) unknown (My University, 1887)
Carrying Concealed Weapons Prohibited, § 105: Prohibited the carrying of a concealed pistol or firearms, slungshot, brass knuckles, or knuckles of lead, brass or other metal or material , or any sandbag, air guns of any description, dagger, Bowie knife, or instrument for cutting, stabbing or striking, or other dangerous or deadly weapon, instrument or device.
Keywords: CARRY - CONCEALED